Trunk Control Inhibition and Balance Training Have an Effect on Balance Control in Children with Cerebral Palsy - Yenri Lisna; Anshar Anshar; Tiar Erawan; Hendrik Hendrik (Health Notions, 2021)
Cerebral palsy is a major cause of movement and posture disorders in children. This condition is a non-progressive motor disorder caused by lesions or brain anomalies that arise in the early stages of a child's development but can change over time due to the growth and plasticity of the development and maturation of the child's central nervous system. The overall prevalence of data collected until 2013 the incidence of Cerebral Palsy was 2.11 per 1000 live births. This study aims to determine the effect of providing balance training intervention and trunk control inhibition on changes in trunk balance control in Cerebral Palsy children. This research is an experimental study with a pre-test – post-test two control group design. The research was conducted at Dr. Hospital. Wahidin Sudirohusodo Makassar, with a sample size of 30 people who were randomly divided into 2 groups, namely 15 people in the group given the balance training intervention and 15 people in the group given the trunk control inhibitor. Balance control capability data was measured using the Trunk Control Measurement Scale (TCMS). The results of the Wilcoxon test analysis showed that there was a significant effect on the provision of balance training (p=0.002) and trunk control inhibition (p=0.007) to improve balance control in children with cerebral palsy. Based on the Mann-Whitney test analysis, it was found that there was no significant difference (p= 0.683) between balance training and trunk control inhibition on changes in balance control. Keywords: balance training; inhibition trunk control; trunk control measurement scale; balance control; cerebral palsy